2015
DOI: 10.1080/15205436.2014.995767
|View full text |Cite
|
Sign up to set email alerts
|

Sports Draped in the American Flag: Impact of the 2014 Winter Olympic Telecast on Nationalized Attitudes

Abstract: A total of 525 U.S. respondents participated in a survey of nationalized attitudes surrounding four qualities (patriotism, nationalism, internationalism, and smugness) and their relationship to Olympic media consumption. Four data collection points were used: three months prior to the Sochi Games, immediately before the Opening Ceremonies, immediately after the Closing Ceremonies, and one month after the Sochi Games. Results indicated that the amount of Olympic media consumption significantly heightened respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…This article understands televised football as a cultural text, wherein among other things hegemonic assumptions and understandings surrounding race/ethnicity, gender, and nationality are expressed and reinforced (Billings et al, 2015). These hegemonic discourses are neither stable nor fixed, and its meanings are in a constant process of defending or adapting to competing discourses (Hall, 1986).…”
Section: Theoretical Framework Sport Media Critical Race Theory (Crtmentioning
confidence: 99%
“…This article understands televised football as a cultural text, wherein among other things hegemonic assumptions and understandings surrounding race/ethnicity, gender, and nationality are expressed and reinforced (Billings et al, 2015). These hegemonic discourses are neither stable nor fixed, and its meanings are in a constant process of defending or adapting to competing discourses (Hall, 1986).…”
Section: Theoretical Framework Sport Media Critical Race Theory (Crtmentioning
confidence: 99%
“…The literature on media and sports shows that both groups of scholars appreciate the others' perspective (e.g., Billings et al, 2015;Butterworth, 2010). Yet we are not aware of any other study that has used both methods in conjunction with one another.…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation for this is that participants were not asked to report on the type of content they consumed that could foster or diminish nationalistic attitudes. Billings et al (2015) found that when Americans watched the winter Olympics, there were no heightened patriotic feelings reported while Lin (2009) found that Americans supported the red, white, and blue more during the coverage of the Iraqi war by the American media. Thus, future studies in Kenya should explore the specific media content being selected and consumed in relation to the patriotic feelings harbored by Kenyans.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The levels of love for Kenya as reported by Kenyans was captured using the Patriotism scale developed by Livingstone and Markham (2008) and used by Billings, Brown, and Brown-Devlin (2015). The scale measured the degree to which the participant agreed or disagreed with 6 items provided, such as "I love my country," and "I am very proud to be from my country", with the response alternatives ranging from 1= Strongly Disagree to 5=Strongly Agree.…”
Section: Patriotismmentioning
confidence: 99%
See 1 more Smart Citation